Book Reviews - Rosenblatt, Arnold; Weinberg, Philip; Schechter, Minda (Columbia Journal of Environmental Law, 2020)
THE SOCIAL GAMBLE. By Richard J. Tobin. Lexington, Mass.: D. C. Heath & Co., 1979. Pp. xvi, 174. 17.00 AMERICAN ENERGY CHOICES BEFORE THE YEAR 2000. Edited by Elihu Bergman, Hans A. Bethe and Robert E. Marshak. Lexington, Mass.: D. C. Heath & Co., 1978. Pp. viii, 150. 14.50. ENERGY AND NATURAL RESOURCES LAW: CASES AND MATERIALS. By William H. Rodgers, Jr. St. Paul: West Publishing Co., 1979. Pp. iii, 995. 22.95.